Determination of the standardized uptake value (SUV) of 18F-FDG in PET/CT in the simulation of lesions less than or equal to 10 millimeters in air and lung mannequin - Sequeiros-Palomino, Itala (2025)
Positron emission tomography (PET) images contribute to the metabolic evaluation of lesions at all stages using the radiopharmaceutical 18F-FDG (Fluorine-18-fluorodeoxyglucose); oncology is its main indication. The most used parameter is the standardized uptake value (SUV). Studies suggest further research into the metabolic quantification of lesions ≤ 10 mm in PET. Objective: To determine the accuracy of SUV in the simulation of lesions ≤ 10 mm in air and lung mannequin with point radioactive sources of  18F-FDG. Methods: Experimental study based on 36 simulations in air and 36 simulations in a lung mannequin. Measures of central tendency were described, and the medians of SUVPET and SUV theoretical in air and lung mannequin were compared using the non-parametric Wilcoxon-Mann-Whitney test. Results: SUV accuracy in simulations of lesions ≤10 mm showed systematic overestimation, greather in air than in the lung mannequin, exceeding the 5% uncertainty recommended by the International Atomic Energy Agency (IAEA). Conclusions: The accuracy percentage of SUVPETmax, SUVPETmed and SUVPETmin values presented a value greather than 5%; the estimates showed significant deviation for this size range, making SUV quantification difficult for lesions smaller than 10mm.